Kinetic study of the oxidation of phenolic derivatives of α,α,α-trifluorotoluene by singlet molecular oxygen [O₂(¹Δg)] and hydrogen phosphate radicals - Rosso, Janina Alejandra (2003)
The oxidation kinetics and mechanism of the phenolic derivatives of α,α,α-trifluorotoluene, 2-trifluoromethylphenol, 3-trifluoromethylphenol (3-TFMP), 4-trifluoromethylphenol and 3,5-bis(trifluoromethyl)phenol, mediated by singlet molecular oxygen, O2(¹Δg), and hydrogen phosphate radicals were studied, employing time-resolved O2(¹Δg) phosphorescence detection, polarographic determination of dissolved oxygen and flash photolysis. All the substrates are highly photo-oxidizable through a O2(¹Δg)-mediated mechanism. The phenols show overall quenching constants for O2(¹Δg) of the order of 106 M⁻¹ s⁻¹ in D2O, while the values for the phenoxide ions in water range from 1.2 × 10⁸ to 3.6 × 10⁸ M⁻¹ s⁻¹. The effects of the pH and polarity of the medium on the kinetics of the photo-oxidative process suggest a charge-transfer mechanism. 2-Trifluoromethyl-1,4-benzoquinone is suspected to be the main photo-oxidation product for the substrate 3-TFMP. The absolute rate constants for the reactions of HPO4•− with the substrates range from 4 × 10⁸ to 1 × 10⁹ M⁻¹ s⁻¹. The 3-trifluoromethylphenoxyl radical was observed as the organic intermediate formed after reaction of 3-TFMP with HPO₄•⁻, yielding 2,2’-bis(fluorohydroxymethyl)biphenyl-4,4’-diol as the end product. The observed results indicate that singlet molecular oxygen and hydrogen phosphate radicals not only react at different rates with the phenols of α,α,α-trifluorotoluene, but the reactions also proceed through different reaction channels.